Sei sulla pagina 1di 11

1.

Sol:

Powered by www.myengg.com

INDEFINITE INTEGRATION

PREVIOUS EAMCET BITS

dx ∫ ( x +1 ) 4x + 3 − 1 1) tan 4x +
dx
(
x +1
)
4x + 3
1
1)
tan
4x
+
3
+

Ans:

4x + 3 = t

2

4dx = 2tdt

c

2)

3tan

1

4x + 3
4x
+
3

x =

t

2

3

4

+

c

3)

=

=

− 1 2 tan 4x + 3 1 tdt 2 ∫ 2 ⎛ t −
− 1
2 tan
4x
+
3
1 tdt
2
2
⎛ t
3
+ 1
t
4
2
dt
=
2 tan
2
t
+ t

+

1

c

t

+

4)

4 tan

c

= 2 tan

1

[EAMCET 2009] 4x + 3 + c
[EAMCET 2009]
4x
+
3
+
c

1

(

4x + 3
4x
+
3

)

+

c

1 dx = tdt 2 ⎛ 2 − sin 2x ⎞ x 2. ∫ e
1
dx
=
tdt
2
⎛ 2
sin 2x
x
2.
e dx
[EAMCET 2009]
⎜ ⎝
1
cos 2x
⎟ ⎠
x
x
x
x
1)
−e
cot x + c
2)
e
cot x + c
3)
2e
cot x + c
4)
−2e cot x + c
Ans: 1
⎛ 2
x
2x
Sol:
2sin x cos x ⎞
e dx
=
(
cosec x
cot x
)
e dx
2
⎜ ⎝
2sin x
x
2
=
e
(
− cot x + cosec x⎤ ⎦ dx
)
xx
x
e
(
−+ cot x
)
c
e
f
()
x
+
f
()
x
dx
=
e f
()
x
+
c

3.

Sol:

If

I

n

n =

=

1)

sin

n

Ans: 1

I

n

=

sin xdx

1

x cos x

sin

n

1

n

then

2)

dx

x sin x v

u

nI

n

(

n

−−

1

)

I

n

cos

n

1

x sin x

2

=

3) – sin

n

1

x cos x

I

n

=

sin

n

1

x

I

I

I

n

n

n

= −

= −

= −

sin

sin

sin

n1

n

n

1

1

(

cos x

)

x cos x

+

x cos x

x cos x

+

+

sin x

−−

(

(

(

I

n

1

n

n

n

1

1

1

)

sin x

sin

n2

)(

)

(

)(

n

2

)

n

2

(

xdx

1

()

n

1

I

cos x

(

n

sin

n

2

1

nI

cos x dx

)

dx

n

sin

n

(

n

I

n2

)

n

2

(

)(

x

)

)

xdx

1

)

=

sin

[EAMCET 2009]

n

4)

1

cos

x cos x

n

1

x sin x

Powered by www.myengg.com

Powered by www.myengg.com

Indefinite Integration

4.

Sol:

If

1)

e

e

x

x

1

⎜ ⎝

1

sin x ⎞ ⎟ ⎠

cos x

cot

x

2

⎟ ⎠

Ans:3

dx

=

2)

f

(

x

e

x

)

+

c then f (x)

cot

x

2

⎠ ⎟

=

3)

x

e cot

⎛ x x ⎞ 1 − 2sin cos ⎜ ⎟ ⎡ 1 ⎤ x 2
x
x
1
2sin
cos
1
x
2
2
x
2
e
⎟ dx
=
e
cos ec
xx cot
dx
x
2
22
2
⎣ ⎢
⎦ ⎥
2sin
2
x
xx
x
=− ⎛ ⎜
e
cot
+
c
e
f
()
x
+
f
()
x
dx
=
e f
()
x
+
⎡ ⎣
⎡ ⎣
⎦ ⎤
2
⎠ ⎟
x
x
)
x
∴ f (
= −
e
cot 2

c

x

2

⎤ ⎦

⎠ ⎟

[EAMCET 2008]

4)

e

x

cot

⎜ ⎝

x

2

⎟ ⎠

n cx 5. If I = ∫ x e dx for n ≥ 1 then
n
cx
5.
If I
=
x e
dx
for n
1 then c.I
+=
n.I
[EAMCET 2008]
n
n
n1
n
cx
n
cx
n
cx
1)
x e
2)
x
3)
e
4)
x
+ e
Ans: 1
n
cx
x
e
Sol:
I
= ∫
.
dx
n
u
v
cx
e
n
cx
n
1
x
e
dx
n.x
.
⎟ ⎞ dx
c
cx
e
n
n
n
cx
Ix =
I
CI
=
x e
nI
n
n
1
n
n
1
c
c

6.

Sol:

7.

C.I

n

+

nI

If

e

x

(

x e

1+ x .sec

=

)

n

n1

1)

(

cos xe

x

)

Ans:

Let

xe

x

= t

cx

(

2x

xe

2)

(

e

x.e

x

+ e .1 dx = dt

x

)

x

(

)

x +1 dx = dt

I

e

x

1

e

x

+

1

dx

=

f

(

x

)

+

c

)

dx =+f

x

(

)

(

sin xe

x

)

c then f

(

x

3)

)

=

2 tan

1

x

then f(x) is equal to

e

x

(

)

x +1 sec

(

2x

xe

)

= tan t +⇒c

(

tan xe

x

f

(

x

)

= tan

(

xe

x

)

4)

dx =

)

+ c

(

tan xe

x

[EAMCET 2008]

)

2

sec tan

[EAMCET 2007]

Powered by www.myengg.com

Powered by www.myengg.com

Indefinite Integration

Sol:

8.

1)

(

2log e

x

Ans: 3

+1

)

2)

log

(

e

2x

1

)

3)

(

2log e

x

+1

)

x

x xxx 2e ( x − e + 1 ) eee1 +−− = ∫ dx
x
xxx
2e
(
x
e
+
1
)
eee1
+−−
=
dx
dx
x
x
e1
+
e1
+
x
x
x
2e
e
+ 1
e
=
dx
dx
=
2 ∫
dx
1dx
x
x
x
e1
+
e1
+
e
+ 1
x
= 2log
e
+−+
1
x
c
(
x
∴f
x
)
= 2log e +−1
(
)
x
1
x
1
tan
dx =
1
+
x
⎟ ⎟ ⎠

4)

log

(

e

2x

+1

)

[EAMCET 2007]

1 1 − 1 2 − 1 2 1) ( x cos x −− 1
1
1
− 1
2
− 1
2
1)
(
x cos
x
−− 1
x
)
+
c
2)
(
x cos
x
+
1
x
)
+
c
2
2
1
1
− 1
− 1
3)
(
2
x sin
x
−− 1
x
)
+
c
4)
(
2
x sin
x
+
1
x
)
+
c
2
2
Ans:
Sol:
Put x = cos2θ
1 cos 2
θ
1
1
− 1
1
=
∫ tan
dx
=
cos
x.x
.xdx
1 cos 2
+
θ
2
2
⎟ ⎟ ⎠
1
x
1
12x
− 1
(
2
)
1
=
∫ tan
tan
θ
dx
=
cos
x.x
dx
2
2
2
1
x
1
1
1
2
=
θdx =
1 cos
xdx
=
cos
x.x
−× 1
2
1
x
+
c
2
2 ⎣ ⎢
2
⎦ ⎥

9.

Sol:

1 − 1 1 − 1 ⎡ 2 ⎤ = x.1.dx ∫ cos = cos
1
1
1 − 1
2
= x.1.dx
cos
=
cos
x.x
−− 1
x
+
c
2
2 ⎣
sin x
+
8cos x dx
∫ 4sin x
+ 6cos x
1
1)
x
+
log
4sin x
++ c
6cos x
2) 2x
+ log
2sin x
+ 3cos x
+ c
2
1
3) x
+
2log
2sin x
++ c
3cos x
4)
log
4sin x
+ 6cos x
+ c
2
Ans: 1
a cos x
+
bsin x
ac
+−⎞⎛
bd
ad
bc ⎞
dx
=
x
+
log
(
cos x
++ dsin x c
)
⎟⎜
22
22
ccos x
+
dsin x
⎝ ⎜
c
++
d
⎠⎝
c
d
⎟ ⎠

Powered by www.myengg.com

[EAMCET 2007]

Powered by www.myengg.com

Indefinite Integration

10.

Sol:

8cos x + 1.sin x ⎛ 48 +−⎞⎛ 4 32 6 ⎞ ∫ dx =
8cos x
+
1.sin x
48
+−⎞⎛
4
32
6 ⎞
dx
=
x
+
log
6cos x
+
4sin x
⎟⎜
6cos x
+
4sin x
⎜ ⎝
36
++
16
⎠⎝
36
16
1
=
x
+
log
6cos x
++ 4sin x c
2
If
dx
=
g
(
x
)
+
c
then g(x) is equal to

2 cos

1)

3

Ans:

1 x

x ∫ 3 x ⎞ 3 ⎛ 1 − a ⎜ ⎟ 3 a ⎝
x
3
x
3 ⎛
1 −
a ⎜
3
a

dx

=

3 ⎛ x ⎞ − 1 2) 2 sin ⎟ 3 3 ⎜ a ⎝
3
x
1
2)
2 sin
3
3 ⎜
a
1
x/a
dx
a
3
x ⎞
1
− ⎜ ⎝
a ⎟ ⎠
⎛ 3 ⎞ x − 1 3) 2 sin ⎜ 3 3 ⎜ a ⎝
3
x
1
3)
2 sin
3
3 ⎜
a
⎠ ⎟ ⎟
x
2/3
Let
=
sin
θ

a

+ c

4)

[EAMCET 2006]

2 1

cos

3 ⎜ ⎝

x

a

⎠ ⎟

1/3 1 ( sin θ ) cos θ 2 2 − 1 = ∫ ××
1/3
1
(
sin θ
)
cos θ
2
2
1
=
×× 2a
d
θ
dx
=
a.
(
sin
θ
)
3
cos
θθ d
1/3
a
2
3
1
sin
θ
(
sin θ
)
3
2
2
2a
cos θ
=
1.d
θ⇒
θ+
c
dx
=
×
d
θ
1/3
3
3
3
(
sin θ
)
3
2
x
1
=
sin
c
3
3
a
⎟ ⎟ ⎠ +
3
2
x
(
)
1
g
x
=
sin
c
3
3
a
⎟ ⎟ ⎠ +
dx
11.
If
fx
(
)
+
c
then f(x) is equal to
[EAMCET 2006]
2
x
+
2x
+
2 =

Sol:

tan

Ans: 1

1)

1

(

x

+

dx

(

x1 +

f

()

x

)

2

=

+

1

tan

1

)

= tan

1

(

x

+

2)

1

1

(

)

x

2 tan

+

)

1 c

1

(

x

+

1

)

3)

tan

1

(

x

+

1

)

12. Observe the following statements :

A :

R :

f

2

1

+

x

x

2

e

2

x1

x

dx

1

()

x

.e

f(x)

dx = f

=

e

2

x1

x

+

c

()

x + c , then which of the following is true ?

4)

3tan

1

(

x

+

1

)

[EAMCET 2006]

1) Both A and R are true and R is the correct reason of A

Powered by www.myengg.com

Powered by www.myengg.com

Indefinite Integration

Sol:

2) Both A and R are true and R is the correct reason of A

3) A is true, R is false

Ans: 3

4) A is false, R is true

R :

f

1

(

x

)

.e

f(x)

dx

A :

⎜ ⎝

1

+

1

x

2

⎟ ⎠

e

⎜ ⎝

x

1

⎠ ⎟

x

dx

Let f(x) = t

f

1

(

x

)

dn = dt

t

e dt = e

t

+ c

= e

f (x)

+ c

Let

⎜ ⎝

1 +

x

1

x

=

t

1

x

2

⎟ ⎠

dx

=

dt

=

t

e dt

=

e

t

x

2

1

e

x

+ c

+=

c

e

x

1

x

+

c

Here A is true and R is false sin x 13. If ∫ dx =
Here A is true and R is false
sin x
13.
If
dx
=
f
(
x
)
+
c
[EAMCET 2005]
cos x
(
1
+
cos x
)
1
+
cos x
cos x
sinx
1
+
sinx
1)
log
2)
log
3)
log
4)
log
cos x
1+ cos x
1+ sin x
sin x
Ans: 1
Sol:
Let cosx = t
– sinxdx = dt
− dt
⎛ −
1
1
=
+
dt
t1
(
+
t
)
⎜ ⎝
t
t
+
1
⎟ ⎠
=
− log t + log | t ++1|
c

14.

Sol:

t + 1 1 + cos x = log + c = log t cos
t
+
1
1
+
cos x
= log
+ c
= log
t
cos x
1
+
cos x
f
(
x
)
=
log
+ c
cos x

x

49

tan

1

(

x

50

)

1

+

x

100

dx

1)

1

50

Ans:

Let

tan

1

(

x

50

)

=

t

=

K

2)

⎣ ⎡

tan

1

50

1

(

+ c

x

50

)

2

+ c

, then K =

3)

1

100

Powered by www.myengg.com

[EAMCET 2005]

4)

1

100

Powered by www.myengg.com

Indefinite Integration

15.

Sol:

1 × 50.x 49 dx = dt 2 + ( 50 ) 1 x 49
1
×
50.x
49 dx
=
dt
2
+ (
50 )
1
x
49
2
x
dx
dt
dt
1
t
1
2
1
=
=
=
=
×
+ c ⇒
⎡ ⎣ tan
50
100
1
+
x
50
t 50
50
2
100
2x
− 1
2
If
∫ sin
dx
=
f
(
x
)
log
1
++ x c
then f(x) =
2
⎜ ⎝
1
+ x
⎟ ⎠
1
− 1
1
1)
2x tan
x
2)
− 2x tan
x
3)
x tan
x
Ans: 1
2x
1
1
sin
dx
= ∫
2 tan
xdx
2
⎝ ⎜
1
+ x
⎟ ⎠
= 2
∫ tan
1 x.1.dx

+

c

[EAMCET 2005]

4) –

x tan

1

x

⎡ 1 ⎤ − 1 = 2 tan x. 1.dx ∫ − ∫ .xdx 2
1
1
=
2
tan
x. 1.dx
.xdx
2
⎣ ⎢
1
+
x
⎦ ⎥
1
2
=
2x tan
x
log
1
++ c
x
f
(
x
)
1
=
2x tan
x
dx
16.
fx
()
+⇒ c
fx
()
=
[EAMCET 2004]
(
x
+
100
)
x
+
99 =
) 1/2
) 1/2
1
1
1)
2
(
x +100
2)
3
(
x +100
3)
2 tan
(
x
+
99
)
4)
2 tan
(
x
+
100
)
Ans: 3
Sol:
Let x + 99 = t 2
dx = 2t dt
x +100 = x + 99 +⇒1
(
)
t
2 +1
dx
2tdt
− 1
=
=
2 tan
( )
t
+
c
(
x
+
100
)
x
+
99
(
t
2 +
1t
)
− 1 (
= 2 tan
x
+
99
)
+
c
f (
x
)
− 1 (
=
2 tan
x
+
99
)
2
3
− x
x
x
17. ∫
.e dx
=
e f
()
x
+⇒
c
f
()
x
=
[EAMCET 2004]
2
1
2x
+
x
x
1 x
+
x
x
1
1) 1
+ 2)
3) 1
4)
1
− x
1 x
+
x
1
1
+
x

Ans:1

Powered by www.myengg.com

Powered by www.myengg.com

Indefinite Integration

Sol:

=

x

2

3

(

x1

)

2

x

.e dx

⇒ −

(

x12

2

)

(

x1

)

2

x

e dx

(

)(

x1x1

+

)

⎤ ⎥ e dx 4

x

=−

2

x1

(

+

x1

)

2

2

 

(

x1

.e .dx

x

)

2

x

x

+

x

1

(

x

+

1

)

2

⎥ ⎦

⇒−

e

⎣ ⎢

x

1

x

⎜ ⎝

1

+

1

x

⎠ ⎟

+⇒ c

fx

(

)

=

1

1

+

x

x

 

cot

x

dx

=−

f

()

x

+

c

f

x

()

=

=

= e


⎢ ⎣

x

c ⇒ f x () = = ∫ = e ⎡ ⎢ ⎢ ⎣ x sin

sin x cos x

1

18.

1) 2

2) – 2⎡ ⎢ ⎢ ⎣ x sin x cos x 1 ⎤ ⎥ ⎦ 18. ∫ 1)

tan x
tan x

+ c

3) – 2

cot x
cot x

[EAMCET 2004]

4)

2

cot x
cot x
Ans: 4 2 2 cot x cos ec x cot x.cos ec x Sol: ∫
Ans: 4
2
2
cot
x
cos ec x
cot x.cos ec x
Sol:
×
dx
=
dx
2
sin
x cos x
cos ec x
cot x
2
cos ec x
=
dx
=−
2
cot x
+
c
cot x
∴f (x) = 2
cot x
2
1x
++
xx
+
19.
dx =
[EAMCET 2003]
x
+
1x +
1
2
3/2
3/2
1)
1x
+
+
c
2)
(
1x
+
)
+
c
3)
1x+
+ c
4)
21+ x
(
)
+ c
2
3

Sol:

Ans: 2 ( 1 ++ x ) x. 1 + = ∫ x dx x
Ans:
2
(
1
++
x
)
x.
1
+
=
x dx
x
+
1x
+
1x + 1x ++ x ⎤ ⎦ = ⎣ ⎡ ∫ dx x + 1x
1x
+
1x
++
x
⎤ ⎦
= ⎣ ⎡
dx
x
+
1x
+
3/2
21
(
+ x
)
= 1+ x dx =
+ c
3
− 1
1
xx
+
20. ∫ (
1
+−
x
x
)
e
dx
=
− 1
1) (
1
+
xe
)
x
+ x
x
+
c
2) (
x
1e
)

Ans:

+

x

1

+ c

3)

xe

x

+

x

1

+

c

Powered by www.myengg.com

[EAMCET 2003]

4)

xe

x

+

x

1

+

c

Powered by www.myengg.com

Indefinite Integration

Sol:

21.

⎜ ⎝

1

−+ 1

x

x

⎞ ⎟ ⎠ e

x

+

1

x

dx

=

Let

e

x.e

x +

1

x

1

x +

xe

x

+

⎜ ⎝

1

x

x

t

⎝ ⎜

1

−+

x

x

=

1

−+ ⎟ ⎞

1

x

2

e

x

+

1

⎠ ⎟

dx

=

=

1.dt = t + c

1

x

+

x +

xe

c

dx

1

cos x

sin x

=

⎢⎜⎟ 1

⎛⎞ 1

⎝⎠ x

1

x

dt

dx

=

dt

e

x

+

1

x

+

x

+

xe

1

x

dx

[EAMCET 2002]

x x x x 1) log 1 + cot + c 2) log 1 −
x
x
x
x
1)
log
1
+
cot
+ c
2)
log
1
tan
+ c
3)
log
1
cot
+
c
4)
log
1
+
tan
+ c
2
2
2
2
Ans: 3
dx
Sol:
1− cos x − sin x
dx
dx
=
=
2
2sin
x / 2
2sin x / 2cos x / 2
x
x
2
2sin
1
cot
2
⎣ ⎢
2
⎥ ⎦
1
x
2
cosec
dx
x
2
2
=
=−
log
1
cot
+ c
x
2
1
cot 2
dx 22. ∫ = 7 + 5cos x 1 ⎛ − 1 1) tan 1x
dx
22.
=
7
+
5cos x
1
1
1)
tan
1x tan
3
⎜ ⎝
3
2
⎞ ⎟ ⎠ +
1
3)
tan
⎝ ⎜
x
− 1
tan
c
7
2
⎞ ⎟ ⎠ +
Ans: 2
dx
Sol:
7 + 5cos x

c

2)

4)

1 ⎛ − 1 tan 1x tan 6 ⎜ ⎝ 6 2 ⎞ ⎟ ⎠
1
− 1
tan
1x tan
6
⎜ ⎝
6
2
⎞ ⎟ ⎠ +
1
4
⎜ ⎝
x
− 1
tan
tan
c
2
⎞ ⎟ ⎠ +

[EAMCET 2002]

c

Powered by www.myengg.com

Powered by www.myengg.com

Indefinite Integration

x 2 1 − tan 2 use cos x = x 2 1 + tan
x
2
1
tan
2
use
cos x =
x
2
1
+
tan
2
x
x
2
2
sec
.
dx
sec
dx
1
2
2
=
x
2
2
x
2
(
)
2
12
+
2 tan
6
+
tan
2
2
Put tanx/2 = t
1
− 1
=
tan
+
C
6

23.

+ tan 2 2 Put tanx/2 = t 1 − 1 = tan + C 6

dx =

[EAMCET 2002]

1 1 x x x x 1) log 3 + 9 −+ c 1 2)
1
1
x
x
x
x
1)
log
3
+
9
−+ c
1
2)
log
3
9
1
+ c
log
log
3
3
1
1
x
x
x
x
3)
log
3
9
−+ c
1
4)
log
9
+
9
1
+ c
log
log
9
3
Ans: 1
x
3
Sol:
dx
x
9
−1
x
3
=⇒t
3x log 3dx = dt
1
dt
1
x
x
=
log
3
+
9
−+ C
1
log 3
(
log 3
)
t
2 − 1
dx
24.
=
[EAMCET 2001]
xx
(
+
9
)

Sol:

1)

2 tan

1

(

x
x

)

+

C

2)

 

2

3

 

3

Ans: 2

 
 

dx

xx + 9 ( )
xx + 9
(
)
 

Let x = t 2

 

,

dx = 2tdt

2tdt

 

tt

(

2

+

9

)

2

dt

==

2

t3

+

2

2

tan

1

t

⎠ ⎟

3

 

⎝ ⎜

3

tan

1

+ C

⎛ x ⎜ ⎜ 3 ⎝ ⎞ ⎟ ⎟ ⎠ +
x
3
⎞ ⎟ ⎟ ⎠ +

C

3)

tan

1 (

x
x

)

+

C

4)

tan

1

⎛ x ⎜ ⎜ 3 ⎝ ⎞ ⎟ ⎟ ⎠ +
x
3
⎞ ⎟ ⎟ ⎠ +

C

Powered by www.myengg.com

Powered by www.myengg.com

Indefinite Integration

2 ⎛ x ⎞ − 1 = tan ⎜ + C ⎜ 3 3 ⎝
2
x
− 1
=
tan
+
C
3
3
⎟ ⎟ ⎠
2
x
25. ∫ (
x +1
)
e dx =
x
2
x
1)
xe
+ c
2) xe
+ c
Ans: 4
2
x
Sol:
∫ (
x +1
)
e dx
2
)
x
∫ (
x
+ 1 + 2x
.e dx
Let f
()
x
= x
2 +⇒1
f′
()
x
= 2x
x
x
∫ ⎣
⎡f
()
x
+ f ′
()
x
⎤ e dx =+f
()
x
.e

c

3)( x +1e

)

x

+ c

[EAMCET 2001]

4) (

x

2

+1e + c

)

x

2 x =+x ( 1e ) + c dx 26. ∫ = [EAMCET 2001] 22
2
x
=+x
(
1e
)
+ c
dx
26.
=
[EAMCET 2001]
22
2
2
a
sin
x
+
b
cos
x
1
a tan x
⎛ a tan x
1
1)
tan
c
2)
tan
− 1
⎜ ⎝
c
ab
⎝ ⎜
b
⎞ ⎟ ⎠ +
b
⎞ ⎟ ⎠ +
1
b tan x
⎛ b tan x
1
3)
tan
c
4)
tan
c
ab
⎝ ⎜
a
⎞ ⎟ ⎠ +
− 1
⎜ ⎝
a
⎞ ⎟ ⎠ +
Ans: 1
2
2
dx
sec xdx
sec
x
Sol:
=
dx
22
2
2
22
2
2
2
2
2
2
2
a
sin
x
+
b
cos
x
a
sin
x sec
x
+
b
cos
x sec
x
a
tan
x
+
b
1
a tan x
1
=
tan
+
C
ab
⎜ ⎝
b
⎟ ⎠

27.

Sol:

e

1)

x

e

(

x

1−+cot x

cot x + c

Ans: 2

cot

2

x

)

dx =

2)

e

x

=

e

x

e

(

x

Let f

1cot

x + cot

2

x

)

dx

(

(

cot x + cosecx

2

x

)

=− cot x f

)

(

dx

x

)

cot x + c

2

= cosec x

e

x

f

()

x

+ f

()

x

dx =+e f

x

()

x

c

x

=−e cot x + c

3)

e

x

cosec + c

Powered by www.myengg.com

[EAMCET 2000]

4)

x

e cosec + c

Powered by www.myengg.com

Indefinite Integration

28.

Sol:

sin

6

x dx = x

cos

8

1) tan 7x + c

Ans: 2

sin

6

x dx = x

cos

8

tan

6

2)

tan

7

x

7

2

x sec xdx

+ c

=

tan

7

x

7

+

c

3) tan 7x

7

+

c

f

()

x

n

f

()

x

dx =

4)

sec

7

⎡ ⎣

f

(

x

)

⎤ ⎦

n

+

1

n

+

1

[EAMCET 2000]

x + c

() x dx = 4) sec 7 ⎡ ⎣ f ( x ) ⎤ ⎦ n

Powered by www.myengg.com